The Landscape of Pediatric Procedural Sedation in the United Kingdom and Irish Emergency Departments; an International Survey Study - Dani Hall; Tadgh Moriarty; Damian Roland; Ronan O'Sullivan; Carol Blackburn; Stuart Hartshorn; Shrouk Messahel; Mark D. Lyttle; PERUKI (Paediatric & Neonatal Pain)
ABSTRACT Approximately 250 000 children undergo pediatric procedural sedation (PPS) in Emergency Departments (ED) in the United Kingdom and Ireland annually. PPS practice in our setting has not been described as fully as other high‐income countries. We aimed to evaluate PPS in EDs in the United Kingdom and Ireland. An online survey was distributed through Paediatric Emergency Research in the UK and Ireland (PERUKI), in June 2020. One respondent per ED completed the survey, including questions on agents, fasting, training, and governance. Of 72 PERUKI sites, 61 (85%) responded, of which PPS was performed in 50 (82%). Internal training packages existed in under half (22/50, 44.0%). Most had a guideline (43/50; 86.0%) and documentation proforma (39/50; 78.0%). Audit databases existed in 24/50 (48.0%). Intravenous ketamine was the most common agent (43/50; 86%), followed by variable concentration nitrous oxide (13/50; 26%). Fasting practices varied widely across sites and agents. We have demonstrated widespread PPS use, but non‐standardized practice. This leads to potential issues of risk and variability across agents, highlighting a need for a sedation package in the United Kingdom and Ireland to standardize practice and data collection. We propose development of a prospective ED sedation registry in the United Kingdom and Ireland to facilitate data collection to support research within this area.